An Innovation in Planning Management for Learning Arabic at Islamic Boarding Schools - Zainul Arifin; Ayu Desrani; Apri Wardana Ritonga; Faishol Mahmoud Adam Ibrahim (Program Studi Manajemen Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2023)
The purpose of this study: first, to find out the type of language boarding program at the Salafiyyah Syafi'iyyah Islamic Boarding School in Situbondo. Second, to find out the planning of programs offered in the language boarding house Salafiyyah Syafi'iyyah Sukorejo Situbondo. This study uses qualitative research with descriptive methods. The data collection is done by observation and interview with the head of the language boarding house. Data analysis in this study consisted of 3 stages: data condensation, data display, and conclusion drawing/verification. The results of this paper inform several things: 1) The type of activity: mufrodat, al-barqi, khitobah (khitobah, khitobah rolling, khitobah akbar), reading books, memorizing, insha ', club studies, competitions (reading books by examining memorization from Arbain and mufrodat and mc traditions, reading news, advertisements, khitobah, debates, and drama). 2) Arabic language program in language boarding house using a SWOT analysis (strengths, weaknesses, opportunities, threats) with the type of short-term planning that is within a year in the form of operational plans to achieve long-term goals.